Pelatihan Pemberdayaan Zakat Berbasis Meunasah Untuk Peningkatan Ekonomi Masyarakat Di Blang Bladeh Kabupaten Bireuen - Khairul Aswadi; Zulfikar Zulfikar; Dina Hendiyani; Murni Murni; Sutoyo Sutoyo; Syarifuddin Syarifuddin (LPPM Universitas Almuslim, 2023)
The purpose of this activity is to increase the empowerment of zakat and the economy of the Blang Bladeh’s community. So far, with an increase in the amount of zakat, the number of poor people has also increased so that it can be perceived that the distribution of zakat is not on target. The right target and the right source of zakat is the target of this activity based on Meunasah. The implementation method used is a combination of socialization and training. The result of this activity is the establishment of an effective zakat management unit, zakat collection and management of zakat distribution for mustahik.